Herbal Combination Effect on the Quality of Semen and Libido in Ongole Cattle Cross-breed - Lukman Affandhy; Dian Ratnawati; Mochamad Luthfi (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
Bulls fertility has an important role to conception, so bulls should have a high libido, high quality semen, and good performance. This study aimed to improve the quality of semen bulls using traditional herbal medicine by utilizing a combination of medicinal plants. The study used 20 heads of Peranakan Ongole (PO) bulls, is divided into four trials traditional herbs, namely Curcuma xhanthorriza, Curcuma eoriginosa, Alpinia galanga, Andrographis paniculata, Piper retrofractum, Eurycom longifolia, Pimpenella purwatjan, each of which is F1 (15%, 15%, 20%, 5%, 30%, 15% and 0%); F2 (15%, 15%, 20%, 5%, 30%, 10% and 5%); F3 (15%, 15%, 20%, 5%, 25%, 20% and 0%); and F4 (15%, 15%, 20%, 5%, 25%, 15% and 0%). Giving the bull 50 g dose of herbal formula every 300 kg of body weight bull mixed with 200 ml honey and 5 eggs. Bulls were given traditional herbal formula once a week orally. The dependent variable of sperm volume, quality of sperm and strength libido were assessed with randomized block design one way. The results showed that all four traditional herbal formulas that are given to PO bulls did not appear to significantly affect the volume of semen and libido for a month with an average volume of 3.8 ± 2.8 cc / ejaculate and libido 159.9 ± 20.2 seconds. Sperm motility, sperm concentration, percentage of live sperm, and sperm abnormalities in PO bulls were given traditional herbal medicine with four different formulas also not significant (P> 0.05); with as well as the color, pH and consistency is still within the normal range. It was concluded that the four herbal formula derived from a mixture of traditional medicine can be given to bulls in order to increase libido and semen quality. It is suggested for granting herbal medicine ingredient formula of traditional medicine that are cheap and easily obtained to bulls.